2003
DOI: 10.1002/pen.10067
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of roofing membrane rubber by ultrasonic devulcanization

Abstract: The recycling of vulcanizates based on EPDM roofing membrane rubber using a new ultrasonic devulcanization reactor with a grooved barrel was carried out. This reactor provided continuous devulcanization at an output as high as 2.52 g/s. Die pressure and ultrasonic power consumption were measured as a function of processing conditions. The mechanical properties of virgin vulcanized and revulcanized roofing membranes were measured. Tensile strength of the revulcanized rubber was found to be similar to that of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 16 publications
2
25
1
1
Order By: Relevance
“…The imposition of ultrasound at amplitudes of 10 and 12.5 μm generated significant additional gel. Gel formation was previously reported for ultrasonically treated SBR21 and EPDM22 gums. It was also reported that a crosslinking reaction in BR took place at high temperatures 25, 26.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…The imposition of ultrasound at amplitudes of 10 and 12.5 μm generated significant additional gel. Gel formation was previously reported for ultrasonically treated SBR21 and EPDM22 gums. It was also reported that a crosslinking reaction in BR took place at high temperatures 25, 26.…”
Section: Resultssupporting
confidence: 61%
“…Many researchers have studied the degradation of polymers in solution,4–7 polymerization in solution,8–11 the modification of the polymer surface,12 the devulcanization of rubber,13–18 and recently copolymerization at the melt interfaces of polymer blends 19, 20. Structure and property changes under the action of ultrasound have also been studied in styrene–butadiene rubber (SBR)21 and ethylene–propylene–diene monomer (EPDM) gums 22…”
Section: Introductionmentioning
confidence: 99%
“…As reported earlier, 22 in the case of EPDM roofing membrane particles, their size was reduced after passing through the extruder in the absence of the action of ultrasound. However, this reduction of the particle size did not change the value of their gel fraction, and this indicated that simple mechanical shearing of the rubber in the extruder did not cause devulcanization.…”
Section: Curing Gel Fraction and Crosslink Densitymentioning
confidence: 50%
“…Isayev et al [34][35] investigated the devulcanization of various rubbers, including EPDM in a reactor consisting of a single screw extruder and an ultrasonic source on the die. The effect of processing parameters and ultrasonic conditions on devulcanization were reported.…”
Section: Recycling Of the Epdm Waste Rubbermentioning
confidence: 99%